Perancangan Sistem Customer Relation Management untuk Mengelola Business Partner Pada Banyuwangi Festival - IBNU ZULKARNAIN; Augustina Asih Rumanti (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
Banyuwangi Festival is an annual event that is a product of regional leading attractions. This event has attracted the attention of tourists from home and abroad, as well as made a significant contribution in improving the economic, tourism and human resources sectors in Banyuwangi. However, the management of Banyuwangi Festival has not used an effective integrated information system. The current ineffectiveness of business partner management is because the follow-up of cooperation is carried out manually at coordination meetings. The purpose of this study is to design an information system that can support effective business partner management, at the Banyuwangi Festival. Odoo's open-source ERP application is used to support the management of business partners on the CRM module. The design of the ERP concept using the Rapid Application Development (RAD) method aims to design system needs that can pay attention to user needs. The result of this study is the effectiveness of monitoring and controlling the progress of business partners for the preparation of the Banyuwangi Festival event which is integrated in the form of a dashboard.